Treatment “non-responders”: the experience of short-term psychoanalytic psychotherapy among depressed adolescents, their parents and therapists - Fiorini, Guilherme; Khoe, Zane; Fonagy, Peter; Midgley, Nick (Frontiers in Psychology, 2024)
Introduction: Short-term psychoanalytic psychotherapy (STPP) is an evidence-based treatment for adolescents with depression, but like all treatment approaches, not all patients benefit from it. Previous investigations of the process of STPP have mostly focused on successful cases, and only a few studies have included the perspectives of young people, their parents, and therapists in the understanding of treatment non-response. Methods: Semi-structured interviews were carried out with young people who were considered 'non-responders' to STPP, as well as with their parents and therapists. These cases were analyzed using a descriptive-interpretative approach. Results: The data analysis revealed three themes: (1) Therapy as a safe space; (2) Can short-term psychotherapy ever be enough?; and (3) Therapists making links and connections that did not make sense to the young people. Discussion: This study's findings indicate that 'poor outcome' psychotherapy does not necessarily equate to a 'poor experience' of psychotherapy, with different stakeholders appreciating the treatment setting as a 'safe space'. However, they also suggest that some felt that a relatively short-term treatment could not lead to substantial change and that young people in STPP might have a more negative view of their outcomes compared to their parents and therapists. Finally, the findings indicate that some interventions made by clinicians in STPP feel wrong or do not make sense to young people, potentially affecting the therapy process.